Battery

By using embossing process on the positive electrode sheet of the lithium-ion battery and adding propyl acetate to the electrolyte, adjusting the depth of the recess and propyl acetate content, the problem of insufficient energy density and service life of lithium-ion batteries under high magnification conditions is solved. Improves lithium excretion problem and improves the safety and dynamic performance of the battery.

CN119208702AActive Publication Date: 2024-12-27ZHUHAI COSMX BATTERY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411708027.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2024-12-27
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Traditional lithium-ion batteries have low energy density, short service life and easy to resolve lithium under high magnification conditions, resulting in increased safety hazards.

Method used

The positive electrode sheet is treated by embossing process, so that one side of the surface has a concave portion and the other side of the surface has a convex portion. Propyl acetate is added to the electrolyte solution, and the ratio of the depth of the concave portion and the content of propyl acetate is adjusted to reduce lithium ion migration. Time difference improves electrochemical reaction efficiency and mechanical strength.

Benefits of technology

It improves the energy density and service life of the battery under high-speed conditions, reduces the risk of lithium excretion, and improves the dynamic balance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208702A_ABST
    Figure CN119208702A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a battery. The battery comprises a positive plate and an electrolyte, the positive plate is provided with a first surface and a second surface which are oppositely arranged along the thickness direction; the first surface is provided with a plurality of concave parts, and the second surface is provided with a plurality of convex parts; the position of the concave part on the first surface corresponds to the position of the convex part on the second surface; the width of the concave part is 0.2 mm to 8 mm; the electrolyte comprises first carboxylic ester, and the first carboxylic ester comprises propyl acetate; the depth h1 of the concave part and the mass content c1 of the first carboxylic ester in the electrolyte meet the condition that h1 / c1 is greater than or equal to 5 and less than or equal to 200, and the unit of h1 is [mu] m. The battery disclosed by the invention has relatively high energy density and relatively long service life under high-rate charging and discharging conditions, and the problem of lithium precipitation can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a battery. Background Art

[0002] Lithium-ion batteries have become an indispensable part of production and life, and the market's requirements for battery performance are constantly increasing. In this context, the performance of the cathode, as a key component of lithium-ion batteries, directly affects key indicators such as battery energy density, power density, cycle life and safety. Traditional cathodes often fail to meet the requirements under high energy and high power requirements, resulting in low battery energy density, short service life and increased safety risks caused by lithium plating.

[0003] Therefore, it is necessary to improve the energy density and service life of the battery under high energy and high power requirements (i.e. high rate conditions), as well as to improve the problem of lithium plating. Summary of the invention

[0004] The purpose of the present invention is to overcome the above problems existing in the prior art and provide a battery. The battery of the present invention adopts an embossing process on the positive electrode sheet and uses an electrolyte with a specific carboxylic acid ester, so that the battery can have a higher energy density and a longer service life under high rate (for example, greater than 2C) charging and discharging conditions, and can effectively improve the lithium precipitation problem.

[0005] In the related art, there are problems that the battery has poor energy density and cycle life under high rate charge and discharge conditions, and is prone to lithium precipitation. If the positive electrode sheet is embossed, one side of the positive electrode sheet has a concave portion and the other side has a convex portion. On the one hand, the specific surface area of ​​the positive electrode sheet can be increased, thereby improving its electrochemical reaction activity; on the other hand, the mechanical strength and conductivity of the positive electrode sheet can be enhanced, which is beneficial to the speed of lithium ion extraction from the positive electrode sheet.

[0006] However, the inventors of the present invention have found that if only the positive electrode sheet is embossed, it will have an adverse effect on the energy density, cycle life and lithium precipitation of the battery under high-rate charge and discharge conditions. The reason is that: in the battery, the positive electrode sheet is embossed so that the distance between the convex portion on the surface of one side of the positive electrode sheet and the adjacent negative electrode sheet is close, and the path for lithium ions to be transmitted from the positive electrode sheet to the negative electrode sheet (or from the negative electrode sheet to the positive electrode sheet) is shorter; while the distance between the concave portion on the other side surface and the adjacent negative electrode sheet is far, and the path for lithium ions to be transmitted from the positive electrode sheet to the negative electrode sheet (or from the negative electrode sheet to the positive electrode sheet) is longer. This will cause a time difference in the migration of lithium ions on both sides of the positive electrode sheet, resulting in uneven lithium deintercalation on both sides of the positive electrode sheet. This uneven lithium deintercalation is likely to cause low energy conversion efficiency and lithium precipitation on the surface of the negative electrode sheet, resulting in a decrease in the cycle capacity retention rate of the battery, and even safety risks. Therefore, it is necessary to reduce the time difference in the migration of lithium ions on both sides of the positive electrode sheet to improve the problem of kinetic imbalance on both sides of the positive electrode sheet. Based on the above findings, the inventors of the present invention have conducted a lot of targeted research and proposed the following solutions: The present invention provides a battery, comprising a positive electrode sheet and an electrolyte; the positive electrode sheet comprises a first surface and a second surface arranged opposite to each other in a thickness direction; the first surface comprises a plurality of recesses, and the second surface comprises a plurality of protrusions; the positions of the recesses on the first surface correspond to the positions of the protrusions on the second surface; the width of the recesses is 0.2 mm-8 mm; the electrolyte comprises a first carboxylate, and the first carboxylate comprises propyl acetate; the depth h1 of the recesses and the mass content c1 of the first carboxylate in the electrolyte satisfy: 5≤h1 / c1≤200, wherein the unit of h1 is μm.

[0007] Adding specific carboxylates to the electrolyte can effectively reduce the time difference of lithium ion migration on both sides of the positive electrode sheet. The reason is that: first, adding propyl acetate to the electrolyte can increase the migration rate of lithium ions in the electrolyte and reduce the difficulty of lithium ions being embedded in or removed from the active material. This is because: propyl acetate can surround lithium ions through its polar groups and interact with lithium ions to form a solvation shell. The solvation shell not only enables lithium ions to exist more stably in the electrolyte; and, compared with carbonate solvents, propyl acetate has a smaller interaction force with lithium ions, so it can promote the movement and desolvation process of lithium ions. That is, propyl acetate can accelerate the migration rate of lithium ions, weaken the influence of the difference in migration distance of lithium ions from the concave part to the negative electrode sheet and from the convex part to the negative electrode sheet, reduce the concentration polarization of lithium ions on the surface of the negative electrode sheet due to the action of the electric field, slow down the risks of lithium precipitation and black spots on the surface of the negative electrode sheet, and improve the fast charging ability and cycle capacity of the battery. Second, adding propyl acetate to the electrolyte can reduce the overall viscosity of the electrolyte. The greater the viscosity of the electrolyte, the greater the difference in the migration speed of lithium ions on both sides of the positive electrode. Low-viscosity electrolytes can not only make good contact between lithium ions and the surface of the positive electrode, thereby improving the efficiency of the electrochemical reaction, but also reduce the time difference in the migration of lithium ions on both sides of the positive electrode, so that the dynamics on both sides of the positive electrode are balanced.

[0008] However, if the positive electrode is simply embossed and propyl acetate is added to the electrolyte, the energy density, service life and lithium precipitation of the battery at high rates will be limited. This is because the deeper the depth of the concave portion, the greater the time difference in lithium ion migration on both sides of the positive electrode, and more propyl acetate is needed to reduce the time difference in lithium ion migration on both sides of the positive electrode; conversely, the shallower the depth of the concave portion, the smaller the time difference in lithium ion migration on both sides of the surface positive electrode, and less propyl acetate is needed to reduce the time difference in lithium ion migration on both sides of the positive electrode. Therefore, only when the depth of the concave portion and the content of propyl acetate meet a specific relationship can the two be matched to achieve the best performance of the battery.

[0009] Through the above technical scheme, the present invention has at least the following advantages compared with the prior art: the battery of the present invention has a higher energy density and a longer service life under high-rate charge and discharge conditions, and can effectively improve the lithium plating problem.

[0010] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 FIG. 4 is a schematic cross-sectional view of a positive electrode sheet along the thickness direction in an example of the present invention. DETAILED DESCRIPTION

[0012] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0013] The present invention provides a battery, including a positive electrode sheet and an electrolyte. The positive electrode sheet has a first surface and a second surface arranged opposite to each other in the thickness direction. The first surface may have a plurality of concave portions, and the second surface may have a plurality of convex portions; the position of the concave portions on the first surface corresponds to the position of the convex portions on the second surface. Figure 1 The figure shows a schematic cross-sectional view of a positive electrode sheet in an example of the present invention along the thickness direction. As can be seen from the figure, the positive electrode sheet has a first surface and a second surface arranged opposite to each other along the thickness direction, the first surface has a plurality of concave portions, and the second surface has a plurality of convex portions; the position of the concave portions on the first surface corresponds to the position of the convex portions on the second surface. The width of the concave portions can be 0.2 mm-8 mm, for example, 0.2 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm.

[0014] In the present invention, “several” means that the number of concave portions on one side of the positive electrode sheet is greater than or equal to 2; and the number of convex portions on the other side of the positive electrode sheet is greater than or equal to 2.

[0015] In the present invention, the electrolyte may include a first carboxylate, and the first carboxylate includes propyl acetate.

[0016] In the present invention, the depth h1 of the recess and the mass content c1 of the first carboxylic acid ester in the electrolyte satisfy: 5≤h1 / c1≤200, for example, 5, 6, 7, 8, 9, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190 or 200, wherein the unit of h1 is μm.

[0017] In one example, 10≤h1 / c1≤150.

[0018] In one example, 12.5≤h1 / c1≤75.

[0019] In the present invention, the positive electrode sheet can be prepared by embossing to obtain a positive electrode sheet containing a plurality of concave portions and corresponding convex portions. It can be understood that "the position of the concave portion on the first surface corresponds to the position of the convex portion on the second surface" means that: the projection of the concave portion in the thickness direction of the positive electrode sheet and the projection of the convex portion in the thickness direction of the positive electrode sheet at least partially overlap; for example, the former (the projection of the concave portion in the thickness direction of the positive electrode sheet) completely covers the latter (the projection of the convex portion in the thickness direction of the positive electrode sheet); for another example, the latter completely covers the former; for another example, the two partially overlap.

[0020] In the present invention, the projection area of ​​the concave portion in the thickness direction of the positive electrode sheet is 80%-120% of the projection area of ​​the convex portion in the thickness direction of the positive electrode sheet, for example, 80%, 90%, 100%, 110% or 120%.

[0021] In the present invention, the depth h1 of the concave portion may be 3-40, where the unit of h1 is μm; for example, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm.

[0022] In one example, h1 is 5-30, and the unit of h1 is μm.

[0023] When the depth of the recess is shallow (for example, less than 3μm), the specific surface area of ​​the positive electrode sheet is not significantly improved, and the electrochemical activity of the positive electrode sheet and the lithium ion deintercalation speed are not obvious; when the depth of the recess is deep (for example, greater than 40μm), the positive electrode sheet may have an overvoltage problem, which will not only affect the transmission of lithium ions in the positive electrode sheet, but also may cause the positive electrode collector to break, causing safety risks. In addition, if the depth of the recess is too deep, the kinetic difference on both sides of the positive electrode sheet will be too large, and the effect of reducing the difference by adding the first carboxylate alone is limited. On the premise that h1 / c1 meets a specific range, when the depth of the recess is within a specific range, the closely arranged positive electrode active material particles can form better ion channels and enhance the migration of lithium ions in the electrolyte.

[0024] In the present invention, the depth h1 of the concave portion refers to the vertical distance from the lowest point in the concave portion to the surface of the positive electrode sheet. The depth h1 of the concave portion can be measured by conventional methods in the art, such as using a scanning electron microscope (SEM) or a 3D profilometer to measure the depths of at least 20 concave portions or all concave portions on the surface of one side of the positive electrode sheet and taking the average value.

[0025] In the present invention, the shape of the projection of the recess in the thickness direction of the positive electrode sheet is not limited, and can be circular or rectangular. When the shape of the projection of the recess in the thickness direction of the positive electrode sheet is circular, the width of the recess is the diameter of the circle; when the shape of the projection of the recess in the thickness direction of the positive electrode sheet is non-circular, the width of the recess is the equivalent diameter of a circle with the same area as the non-circular. The spacing of the recesses can be 0.5mm-8mm, for example, 0.5mm, 1mm, 2mm, 3mm, 4mm, 5mm, 6mm, 7mm or 8mm. The width of the recess and the spacing of the recess can be obtained by conventional methods in the art, for example, by SEM, at least 10 recesses are selected on the surface of the positive electrode sheet, the width of each recess is measured, and the average value is taken; at least 10 groups of adjacent recesses are selected on the surface of the positive electrode sheet, the shortest distance between the edges of each group of recesses is measured, and the average value is taken.

[0026] In one example, the width of the recess is 0.2 mm-4 mm.

[0027] In one example, the width of the recess is 0.2 mm-3 mm.

[0028] In one example, the interval between the recesses is 1 mm-4 mm.

[0029] In the present invention, the height h2 of the protrusion may be 2 μm-40 μm, for example, 2 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm.

[0030] In one example, the height h2 of the protrusion is 4 μm-30 μm.

[0031] In the present invention, the height h2 of the convex portion refers to the vertical distance from the highest point on the convex portion to the surface of the positive electrode sheet. The height h2 of the convex portion can be measured by conventional methods in the art, such as using a SEM or a 3D profilometer to measure the heights of at least 20 convex portions or all convex portions on the surface of one side of the positive electrode sheet and taking the average value.

[0032] In the present invention, the width of the protrusion may be 0.2 mm-8 mm, for example, 0.2 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm.

[0033] In the present invention, the shape of the projection of the convex portion in the thickness direction of the positive electrode sheet is not limited, and can be circular or rectangular. When the shape of the projection of the convex portion in the thickness direction of the positive electrode sheet is circular, the width of the convex portion is the diameter of the circle; when the shape of the projection of the convex portion in the thickness direction of the positive electrode sheet is non-circular, the width of the convex portion is the equivalent diameter of a circle with the same area as the non-circular. The spacing of the convex portions can be 0.5mm-8mm, for example, 0.5mm, 1mm, 2mm, 3mm, 4mm, 5mm, 6mm, 7mm or 8mm. The width of the convex portion and the spacing of the convex portion can be obtained by conventional methods in the art, for example, by SEM, at least 10 convex portions are selected on the surface of the positive electrode sheet, the width of each convex portion is measured, and the average value is taken; at least 10 groups of adjacent convex portions are selected on the surface of the positive electrode sheet, the shortest distance between the edges of each group of convex portions (that is, the shortest distance between the orthographic projections formed by each group of convex portions on the surface of the positive electrode sheet) is measured, and the average value is taken.

[0034] In one example, the width of the protrusion is 0.2 mm-4 mm.

[0035] In one example, the width of the protrusion is 0.2 mm-3 mm.

[0036] In one example, the pitch of the protrusions is 1 mm-4 mm.

[0037] <Electrolyte> In the present invention, the mass content c1 of the first carboxylic acid ester may be 10%-80%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%.

[0038] In one example, c1 is 40%-60%.

[0039] When the mass content of the first carboxylate in the electrolyte is low (for example, less than 10%), the electrolyte is not effective in reducing the kinetic difference on both sides of the positive electrode sheet, and there is a significant difference in the migration of lithium ions on both sides of the positive electrode sheet, resulting in uneven lithium deintercalation on the surface of the negative electrode sheet, which makes it easy to precipitate lithium, causing the capacity retention rate of the battery to decrease or even drop; and when the mass content of the first carboxylate is high (for example, greater than 80%), it will affect the high temperature performance of the battery.

[0040] In the present invention, the mass content c1 of the first carboxylic acid ester in the electrolyte can be measured by conventional methods in the art, such as using GC-MS.

[0041] In one example, the first carboxylic acid ester is propyl acetate (PA).

[0042] In the present invention, the electrolyte may further include a first lithium salt. The first lithium salt includes at least one of lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0043] The specific first lithium salt exhibits higher conductivity and lithium ion migration number within the normal temperature range, which can increase the number of lithium ion migrations in the electrolyte, thereby improving the overall kinetic performance of the battery. More lithium ions are involved in the formation of solvation shells and desolvation, which is beneficial to enhancing the electrochemical reaction activity on the negative electrode sheet. Therefore, the first lithium salt also has good compatibility with the positive electrode sheet of the present invention, which can further reduce the time difference of lithium ion migration on both sides of the positive electrode sheet, improve the energy density and service life of the battery under high-rate charge and discharge conditions, and improve lithium precipitation.

[0044] In one example, the first lithium salt includes LiFSI.

[0045] In the present invention, the mass content c2 of the first lithium salt and the mass content c1 of the first carboxylate in the electrolyte satisfy: 2.5≤c1 / c2≤100, for example, 2.5, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100.

[0046] In one example, 5≤c1 / c2≤20.

[0047] The first lithium salt can not only increase the number of lithium ion migration, but also improve the overall high temperature performance and electrochemical stability of the electrolyte. However, too much first lithium salt will significantly increase the viscosity of the electrolyte, resulting in an increase in the time difference in lithium ion migration on both sides of the positive electrode, which is not conducive to the energy density, service life and lithium precipitation of the battery under high-rate charge and discharge conditions. Therefore, when adding the first lithium salt, it is necessary to regulate the relationship between the first lithium salt and the first carboxylate, so that the content of the first lithium salt and the first carboxylate is adapted to achieve the first lithium salt. On the premise that the effect of the viscosity of the electrolyte is small, the positive effect of the first lithium salt on the migration rate of lithium ions is further improved.

[0048] In the present invention, the mass content c2 of the first lithium salt in the electrolyte may be 0.5%-10%, for example, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0049] In one example, c2 is 2%-8%.

[0050] In the present invention, the mass content c2 of the first lithium salt in the electrolyte can be measured by conventional methods in the art, such as ion chromatography.

[0051] In the present invention, the electrolyte may further include a first additive. The first additive includes at least one of 1,3-propane sultone (PS), 1,3-propylene sultone (PST), 2,4-butane sultone, 1,4-butane sultone, propylene sultone, butane sultone, methylene disulfonate, dimethyl sulfate, vinyl sulfate (DTD), 4-methyl-vinyl sulfate, methyl vinyl sulfate, propylene sulfate, and vinyl sulfite.

[0052] In one example, the first additive includes PS and DTD, wherein the mass ratio of PS to DTD is 2-8, for example, 2, 3, 4, 5, 6, 7 or 8.

[0053] In the present invention, the mass content c3 of the first additive in the electrolyte and the mass content c2 of the first lithium salt in the electrolyte satisfy: 0.07≤c2 / c3≤10, for example, 0.07, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.

[0054] In one example, 0.4≤c2 / c3≤4.

[0055] In one example, 0.6≤c2 / c3≤2.

[0056] Adding the first lithium salt to the electrolyte will cause the battery to easily produce gas under high-temperature storage. Therefore, it is necessary to add the first additive in coordination and reduce the adverse effect of the first lithium salt on the high-temperature storage performance of the battery by regulating the content relationship between the first lithium salt and the first additive.

[0057] In the present invention, c3 is 0.1%-7%, for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6% or 7%.

[0058] In one example, c3 is 0.5%-5%.

[0059] In one example, c3 is 2%-5%.

[0060] In the present invention, the mass content c3 of the first additive in the electrolyte can be measured by conventional methods in the art, such as by GC-MS.

[0061] In the present invention, the electrolyte may further include a second lithium salt. The second lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium difluorobisoxalatophosphate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide and tris(trifluoromethylsulfonyl)methyllithium.

[0062] In the present invention, the sum of the mass contents of the first lithium salt and the second lithium salt in the electrolyte may be 10%-22%, for example, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21% or 22%.

[0063] In the present invention, the electrolyte may further include a second additive, wherein the second additive includes at least one of fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinylethylene carbonate (VEC) and tripropargyl phosphate.

[0064] In the present invention, the electrolyte may further include an organic solvent. The organic solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), propyl propionate (PP), ethyl butyrate (EB), ethyl acetate (EA), difluoroethyl acetate (DFEA), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC).

[0065] <Positive electrode> In the present invention, the positive electrode sheet may include a positive electrode active material. The positive electrode active material may include a first particle and / or a second particle. The first particle includes a chemical formula of LiNi x1 Co y1 Mn z1 M 1 a1 O2 substances, 0.5≤x1≤0.95, 0.01≤y1≤0.2, 0.01≤z1≤0.4, 0≤a1≤0.1, M 1 The second particles include at least one of Al, Mg, Y, W, B, Zr, Ti, Sr, Si, La and Nb. The second particles include a chemical formula of LiNi x2 Co y2 Mn z2 M 2 a2 O2 substances, 0.5≤x2≤0.95, 0.01≤y2≤0.2, 0.01≤z2≤0.4, 0≤a2≤0.1, M 2Includes at least one of Al, Mg, Y, W, B, Zr, Ti, Sr, Si, La and Nb.

[0066] In one example, the first particles include single crystal particles, and the second particles include polycrystalline particles.

[0067] In one example, the first particles are single crystal particles, and the second particles are polycrystalline particles.

[0068] In one example, the positive electrode active material includes the first particles and the second particles.

[0069] Single crystal particles have excellent structural stability due to their uniform internal crystal structure, consistent grain orientation, and the absence of grain boundaries; however, the large spacing between single crystal particles will increase the Li + The transmission distance of lithium ions is shortened, which reduces the transmission efficiency of lithium ions and makes the capacity and rate performance of the material worse. Polycrystalline particles are composed of several primary particles, and the grain boundaries inside them have a certain adverse effect on the structural stability of the material itself. In addition, the risk of side reactions between the primary particles in the polycrystalline particles and the electrolyte is high, which will further increase the possibility of structural collapse of the polycrystalline particles during the cycle. However, due to the small size of the primary particles in the polycrystalline particles, the Li + transmission distance, therefore, is beneficial to Li + The use of polycrystalline particles and single crystal particles can reduce the internal resistance of the positive electrode to a certain extent, increase the rate of lithium ion insertion and extraction in the positive electrode, and thus improve the cycle performance and rate performance of the battery.

[0070] In the present invention, the mass content of the first particles in the positive electrode active material may be 50%-80%, for example, 50%, 55%, 60%, 65%, 70%, 75% or 80%. The mass content of the second particles in the positive electrode active material may be 20%-50%, for example, 50%, 45%, 40%, 35%, 30%, 25% or 20%.

[0071] By further controlling the mass content of the first particles in the positive electrode active material, it is beneficial to increase the transmission rate of lithium ions in the positive electrode sheet, reduce the risk of side reactions between the positive electrode active material and the electrolyte, and improve the battery's cycle performance and rate performance.

[0072] In the present invention, the average particle size of the first particles may be 1 μm-6 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or 6 μm. The average particle size of the second particles may be 6 μm-15 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm.

[0073] In the present invention, the average particle size of the first particles and the average particle size of the second particles can be tested by conventional methods in the art, such as SEM, taking a cross-sectional image of the positive electrode sheet, selecting at least 20 first particles or 20 second particles in the image, measuring the particle size of each particle, and taking the average value.

[0074] In the present invention, the median particle size Dv50 of the first particles may be 1 μm-6 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or 6 μm. The median particle size Dv50 of the second particles may be 6 μm-15 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm.

[0075] In the present invention, the median particle size Dv50 of the first particles and the median particle size Dv50 of the second particles can be measured by conventional methods in the art, such as a laser particle size analyzer.

[0076] In the present invention, the specific surface area of ​​the first particles can be 0.5 m 2 / g-1.4m 2 / g, for example 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g or 1.4m 2 / g. The specific surface area of ​​the second particles can be 0.3m 2 / g-1m 2 / g, for example 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g or 1m 2 / g.

[0077] In the present invention, the specific surface area of ​​the first particle and the specific surface area of ​​the second particle can be measured by conventional methods in the art, such as the BET method.

[0078] In the present invention, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector. The positive electrode active material layer may include the positive electrode active material. The positive electrode active material layer may also include a positive electrode conductive agent and a positive electrode binder. The positive electrode conductive agent may include a conductive agent conventionally used in the art, for example, including at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber and carbon nanotubes (including at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes). The positive electrode binder may include a binder conventionally used in the art, for example, including at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene and polyethylene oxide.

[0079] In the present invention, based on the total mass of the positive electrode active material layer, the content of the positive electrode active material can be 90%-99.8% (for example, 90%, 92%, 94%, 96%, 98%, 99% or 99.8%), the content of the positive electrode conductor can be 0.1%-5% (for example, 5%, 4%, 3%, 2%, 1%, 0.5% or 0.1%), and the content of the positive electrode binder can be 0.1%-5% (for example, 5%, 4%, 3%, 2%, 1%, 0.5% or 0.1%).

[0080] <Diaphragm> In the present invention, the battery may further include a separator. The separator may include a substrate layer and a glue layer. The glue layer is located on at least one outer surface of the separator and faces the positive electrode sheet.

[0081] Embossing the positive electrode sheet will increase the gap between the positive electrode sheet and the separator, making it difficult for the positive electrode sheet and the separator to fit tightly. Therefore, a glue layer is provided on the outer surface of at least one side of the separator, and the glue layer faces the positive electrode sheet, which can enhance the adhesion between the separator and the positive electrode sheet, so that the two can fit tightly and not fall off during the battery charge and discharge cycle, and can also make the transmission of lithium ions between the positive electrode sheet and the separator smoother, thereby improving the overall dynamic performance of the battery.

[0082] In the present invention, the adhesive layer may include at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-trichloroethylene copolymer, polyvinyl acetate, polyvinyl alcohol, polyethylene oxide, polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate and polyvinylpyrrolidone.

[0083] In the present invention, the thickness H1 of the adhesive layer and the depth h1 of the recess satisfy: 0.007≤H1 / h1≤0.6, wherein the unit of H1 is μm and the unit of h1 is μm; for example, H1 / h1 is 0.007, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5 or 0.6.

[0084] In one example, 0.01≤H1 / h1≤0.35.

[0085] In one example, 0.02≤H1 / h1≤0.1.

[0086] By controlling the relationship between the thickness of the glue layer and the depth of the recess, the adhesion between the separator and the positive electrode sheet can be improved, which is beneficial to further improve the energy density and cycle life of the battery under high-rate charge and discharge conditions.

[0087] In the present invention, H1 may be 0.2 μm-3 μm, for example, 0.2 μm, 0.5 μm, 1 μm, 2 μm or 3 μm.

[0088] In the present invention, the diaphragm may further include a ceramic layer. The ceramic layer may be located on at least one side surface of the substrate layer. The ceramic layer may include at least one of aluminum oxide, aluminum hydroxide, boehmite, silicon oxide, titanium oxide, barium sulfate, silicon nitride, aluminate, aluminum nitride and zirconium oxide.

[0089] In the present invention, the thickness of the ceramic layer can be 1 μm-5 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm. By controlling the thickness of the ceramic layer, the thermal stability of the separator can be enhanced, thereby improving the stability of the battery in a high temperature environment, and further improving the kinetics of lithium ion transmission.

[0090] In one example, the diaphragm includes the substrate layer, the ceramic layer located on at least one side surface of the substrate layer, and the glue layer located on the outer surface of the diaphragm.

[0091] In the present invention, the substrate layer may include polyolefin, for example, polypropylene and / or polyethylene.

[0092] In the present invention, the battery may further include a negative electrode sheet, which may be a negative electrode sheet commonly used in the art.

[0093] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.

[0094] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0095] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.

[0096] The following examples are provided to illustrate the batteries of the present invention.

[0097] Example 1 Prepare the battery as follows: (1) Preparation of electrolyte In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), EC, PC and PP are mixed in a mass ratio of 4:7:29 to form an organic solvent; a first carboxylate PA is added to the organic solvent, c1 is 20%, to form a mixed solvent; a first lithium salt LiFSI is added to the mixed solvent, c2 is 4%, a first additive (PS and DTD are mixed in a mass ratio of 2), c3 is 2%, a second lithium salt LiPF6 based on 11% of the total mass of the electrolyte is added, and a second additive FEC based on 5% of the total mass of the electrolyte is added, and stirred evenly. After passing the moisture and free acid tests, an electrolyte is obtained, wherein the sum of the mass contents of the organic solvent, the first carboxylate, the first lithium salt, the first additive, the second lithium salt and the second additive is 100%; c1 / c2 is 5, c2 / c3 is 2.

[0098] (2) Preparation of positive electrode The positive electrode active material (the first particle and the second particle are mixed in a mass ratio of 65:35, wherein the first particle is a single crystal particle with a chemical formula of LiNi 0.92 Co 0.04 Mn 0.04 O2, with an average particle size of 3 μm; the second particle is a polycrystalline particle with a chemical formula of LiNi 0.9 Co 0.05 Mn 0.05 O2, with an average particle size of 10 μm), conductive carbon black and polyvinylidene fluoride are mixed evenly in a mass ratio of 97.6:1.35:1.05 in N-methylpyrrolidone (NMP), stirred evenly, and a positive electrode slurry is prepared; the positive electrode slurry is evenly coated on the front and back sides of the aluminum foil; the positive electrode sheet with a thickness of 90 μm is obtained by drying and rolling; the positive electrode sheet is then cut and processed using a special roller with protrusions to obtain a positive electrode sheet with a concave portion on one side and a convex portion on the other side; Among them, the width of the concave part is 2 mm, the pitch is 2 mm, and the depth h1 is 15 μm; the width of the convex part is 2 mm, the pitch is 2 mm, and the height h2 is 14 μm; h1 / c1 is 75.

[0099] (3) Preparation of negative electrode sheet Artificial graphite, silicon-carbon material (silicon content is 47%), conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed evenly in a mass ratio of 78.5:20.5:0.5:0.25:0.25, deionized water is added, and the mixture is stirred thoroughly to form a uniform negative electrode slurry; the negative electrode slurry is coated on a copper foil, and the negative electrode sheet is obtained after drying, rolling, cutting and washing.

[0100] (4) Preparation of batteries The positive electrode sheet prepared in step (2), the negative electrode sheet prepared in step (3) and the separator (the substrate layer is a polypropylene film with a thickness of 5 μm, a ceramic layer with a thickness of 1 μm is provided on the surface of one side of the substrate, and a polyvinylidene fluoride adhesive layer with a thickness H1 of 1 μm is provided on the outer surface of the ceramic layer) are wound into a winding core according to a predetermined process, and the electrolyte prepared in step (1) is injected, and the battery is prepared after vacuum sealing, standing, formation, sorting, secondary sealing and other processes; Among them, the glue layer faces the positive electrode; H1 / h1 is 0.067.

[0101] Example 2 The method is carried out in accordance with Example 1, except that the composition of the electrolyte, the preparation of the positive electrode sheet and the thickness of the separator glue layer are as follows: (1) Preparation of electrolyte In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), EC, PC and PP are mixed in a mass ratio of 4:7:29 to form an organic solvent; a first carboxylate PA is added to the organic solvent, c1 is 40%, to form a mixed solvent; a first lithium salt LiFSI is added to the mixed solvent, c2 is 2%, a first additive (PS and DTD are mixed in a mass ratio of 4), c3 is 3%, a second lithium salt LiPF6 based on 13% of the total mass of the electrolyte is added, and a second additive FEC based on 5% of the total mass of the electrolyte is added, and the mixture is stirred evenly. After passing the moisture and free acid tests, an electrolyte is obtained; c1 / c2 is 20, c2 / c3 is 0.67.

[0102] (2) Preparation of positive electrode The positive electrode active material (the first particle and the second particle are mixed in a mass ratio of 50:50, wherein the first particle is a single crystal particle with a chemical formula of LiNi 0.9 Co 0.05 Mn 0.05O2, with an average particle size of 1 μm; the second particle is a polycrystalline particle with a chemical formula of LiNi 0.8 Co 0.1 Mn 0.1 O2, with an average particle size of 6 μm), conductive carbon black and polyvinylidene fluoride are mixed evenly in a mass ratio of 97.6:1.35:1.05 in N-methylpyrrolidone (NMP), stirred evenly, and a positive electrode slurry is prepared; the positive electrode slurry is evenly coated on the front and back sides of the aluminum foil; the positive electrode slurry is dried and rolled in sequence to obtain a positive electrode sheet with a thickness of 90 μm; the positive electrode sheet is then cut and processed using a special roller with protrusions to obtain a positive electrode sheet with a concave portion on one side and a convex portion on the other side; The width of the concave portion is 2.8 mm, the pitch is 4 mm, and the depth h1 is 5 μm; the width of the convex portion is 2.7 mm, the pitch is 4 mm, and the height h2 is 4 μm; and h1 / c1 is 12.5.

[0103] (4) Preparation of batteries The thickness H1 of the adhesive layer is 0.5 μm, and H1 / h1 is 0.1.

[0104] Example 3 The method is carried out in accordance with Example 1, except that the composition of the electrolyte, the preparation of the positive electrode sheet and the thickness of the separator glue layer are as follows: (1) Preparation of electrolyte In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), EC, PC and PP are mixed uniformly in a mass ratio of 4:7:29 to form an organic solvent; a first carboxylate PA is added to the above organic solvent, c1 is 60%, to form a mixed solvent; a first lithium salt LiFSI is added to the above mixed solvent, c2 is 8%, a first additive (PS and DTD are mixed in a mass ratio of 8), c3 is 5%, a second lithium salt LiPF6 based on 7% of the total mass of the electrolyte is added, and a second additive FEC based on 5% of the total mass of the electrolyte is added, and the mixture is stirred uniformly. After passing the moisture and free acid tests, an electrolyte is obtained; c1 / c2 is 7.5, c2 / c3 is 1.6.

[0105] (2) Preparation of positive electrode The positive electrode active material (the first particle and the second particle are mixed in a mass ratio of 80:20, wherein the first particle is a single crystal particle with a chemical formula of LiNi 0.8 Co 0.1 Mn 0.1 O2, with an average particle size of 6 μm; the second particle is a polycrystalline particle with a chemical formula of LiNi 0.7 Co 0.1 Mn 0.2O2, with an average particle size of 15 μm), conductive carbon black and polyvinylidene fluoride are mixed evenly in a mass ratio of 97.6:1.35:1.05 in N-methylpyrrolidone (NMP), stirred evenly, and a positive electrode slurry is prepared; the positive electrode slurry is evenly coated on the front and back sides of the aluminum foil; the positive electrode slurry is dried and rolled in sequence to obtain a positive electrode sheet with a thickness of 90 μm; the positive electrode sheet is then cut and processed using a special roller with protrusions to obtain a positive electrode sheet with a concave portion on one side and a convex portion on the other side; The width of the concave portion is 0.2 mm, the pitch is 1 mm, and the depth h1 is 30 μm; the width of the convex portion is 0.2 mm, the pitch is 1 mm, and the height h2 is 28 μm; and h1 / c1 is 50.

[0106] (4) Preparation of batteries The thickness H1 of the adhesive layer is 0.75 μm, and H1 / h1 is 0.025.

[0107] Example 4 Used to verify the impact of changes to "h1 / c1".

[0108] The same method is carried out with reference to Example 2, except that the composition of the electrolyte is changed as follows: c1 is 60%, c2 is 8%, c3 is 5%, the mass content of the second lithium salt LiPF6 is 7%, and the mass content of the second additive FEC is 5%; Among them, h1 / c1 is 8.3.

[0109] Example 5 Group This group of embodiments is used to verify the influence of the change of the "depth h1 of the recess".

[0110] This group of examples is carried out with reference to Example 1, except that the depth h1 of the concave portion is changed (the width and spacing of the concave portion are kept unchanged), as follows: Example 5a, h1 is 3 μm, h2 is 2 μm; In Example 5b, h1 is 40 μm and h2 is 38 μm.

[0111] Example 6 Group This group of examples is used to verify the influence of the change of "the mass content c1 of the first carboxylic acid ester in the electrolyte".

[0112] This group of examples is carried out with reference to Example 1, except that c1 is changed, as follows: Example 6a, c1 is 10%; Example 6b, c1 is 78%.

[0113] Example 7 Group This group of examples is used to verify the impact of changes in the "first lithium salt".

[0114] This group of examples is carried out with reference to Example 1, except that the first lithium salt is changed, as follows: Example 7a, replacing LiFSI with LiTFSI of the same mass; In Example 7b, the first lithium salt is not added to the electrolyte.

[0115] Example 8 Group This group of examples is used to verify the impact of changes in "the mass content c2 of the first lithium salt in the electrolyte".

[0116] This group of examples is carried out with reference to Example 1, except that c2 is changed, as follows: Example 8a, c2 is 0.5%; Example 8b, c2 is 10%.

[0117] Example 9 Used to verify the impact of changes to "c1 / c2".

[0118] The process is carried out with reference to Example 3, except that the mass content c2 of the first lithium salt in the electrolyte is changed. Specifically, c2 is 2% and c1 / c2 is 30.

[0119] In addition, in order to avoid the influence of the change of c2 / c3 on the observation of the effect of c1 / c2, in Example 10, c3 was changed at the same time, c3 was 3%, and c2 / c3 was 0.67.

[0120] Example 10 Group This group of examples is used to verify the impact of changes in the “first additive”.

[0121] This group of examples is carried out with reference to Example 1, except that the first additive is changed, as follows: Example 10a, the first additive is replaced by the same mass of PS; Example 10b, the first additive is replaced by a combination of PST and DTD of the same mass, wherein the mass ratio of PST to DTD is 2; In Example 10c, the first additive is not added to the electrolyte.

[0122] Example 11 Group This group of examples is used to verify the impact of changes in "the mass content c3 of the first additive in the electrolyte".

[0123] This group of examples is carried out with reference to Example 1, except that c3 is changed, as follows: Example 11a, c3 is 0.5%; Example 11b, c3 is 7%.

[0124] Example 12 Group This group of embodiments is used to verify the impact of the change of "c2 / c3".

[0125] This group of examples is carried out with reference to Example 2 or Example 3, except that c2 / c3 is regulated by changing c3, ​​as follows: Example 12a, carried out with reference to Example 2, except that c3 is 5%, and c2 / c3 is 0.4; Example 12b is carried out with reference to Example 3, except that c3 is 2% and c2 / c3 is 4.

[0126] Example 13 Used to verify the impact of changes in "whether the rubber layer of the diaphragm faces the positive electrode sheet".

[0127] The method is carried out in accordance with Example 1, except that the glue layer in the diaphragm is removed (ie, the diaphragm includes a substrate layer and a ceramic layer located on one surface of the substrate layer).

[0128] Example 14 Group This group of embodiments is used to verify the impact of the change of "H1 / h1".

[0129] This group of examples is carried out with reference to Example 2 or Example 3, except that H1 / h1 is adjusted by changing the thickness H1 of the adhesive layer, as follows: Example 14a, carried out with reference to Example 2, except that H1 is 1 μm and H1 / h1 is 0.2; Example 14b is carried out with reference to Example 3, except that H1 is 0.5 μm and H1 / h1 is 0.017.

[0130] All the above embodiments satisfy the following conditions: the median particle size Dv50 of the first particle is 6 μm-15 μm, the median particle size Dv50 of the second particle is 1 μm-6 μm, and the specific surface area of ​​the first particle is 0.5 m 2 / g-1.4m 2 / g; the median particle size Dv50 of the second particles is 6μm-15μm, and the specific surface area of ​​the second particles is 0.3m 2 / g-1m 2 / g.

[0131] Comparative Example 1 The process is carried out in accordance with Example 1, except that the first carboxylate is not added to the electrolyte.

[0132] Comparative Example 2 The method is carried out in accordance with Example 1, except that the positive electrode sheet is not embossed (ie, the first surface of the positive electrode sheet has no concave portion, and the second surface has no convex portion).

[0133] Comparative Example 3 The process is carried out in accordance with Example 1, except that h1 / c1 is regulated by simultaneously changing the depth h1 of the recess and the mass content c1 of the first carboxylate in the electrolyte. Specifically, h1 is 1 μm, c1 is 78%, and h1 / c1 is 1.28.

[0134] Comparative Example 4 The process is carried out in accordance with Example 1, except that h1 / c1 is controlled by simultaneously changing the depth h1 of the recess and the mass content c1 of the first carboxylate in the electrolyte. Specifically, h1 is 42 μm, c1 is 10%, and h1 / c1 is 420.

[0135] Comparative Example 5 The same process was carried out as in Example 1, except that PA was replaced with EB of the same mass.

[0136] Test Case (1) 25℃ cycle test The batteries prepared in the embodiments and comparative examples were placed at 25° C. for 60 minutes, charged to 4.3V at a constant current of 2C, then charged to 0.05C at a constant voltage of 4.3V, left to stand for 5 minutes, and then discharged to 2.5V at a constant current of 3C, and left to stand for 5 minutes, which was one charge and discharge cycle; the charging / discharging was repeated for 1000 cycles, and the cycle capacity retention rate was recorded, and the results were recorded in Table 1; after 1000 cycles, the battery was fully charged, the battery was disassembled, and the lithium deposition of the negative electrode sheet was observed. If no lithium deposition occurred on the negative electrode sheet, it was recorded as no lithium deposition; if lithium deposition occurred only in the arc area of ​​the core on the negative electrode sheet, it was recorded as slight lithium deposition; if lithium deposition occurred in the arc area of ​​the core and the top and bottom of the core on the negative electrode sheet, it was recorded as lithium deposition; if lithium deposition occurred in the arc area of ​​the core, the top and bottom of the core, and the straight area of ​​the core on the negative electrode sheet, it was recorded as severe lithium deposition, and the results were recorded in Table 1.

[0137] (2) 45℃ cycle test The batteries prepared in the examples and comparative examples were placed at 45°C for 60 minutes, charged to 4.3V at a constant current of 2C, then charged to 0.05C at a constant voltage of 4.3V, left standing for 5 minutes, and then discharged to 2.5V at a constant current of 3C, left standing for 5 minutes. This was one charge and discharge cycle. The charge / discharge was repeated for 600 cycles, and the cycle capacity retention rate was recorded. The results are recorded in Table 1.

[0138] (3) Energy density test The batteries prepared in the examples and comparative examples were charged at 0.7C to the upper voltage limit (4.3V), with a cutoff current of 0.025C, and discharged at 0.5C to the lower voltage limit (2.5V). The discharge capacity and the working platform voltage were output, and the weight of the batteries was measured. The energy density was calculated using the formula: Energy density = discharge capacity × working platform voltage / battery weight. The results are recorded in Table 1.

[0139] Table 1 It can be seen from Table 1 that the battery of the present invention has higher energy density and longer service life under high rate charge and discharge conditions compared with the comparative example, and can effectively improve the lithium plating problem.

[0140] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A battery, characterized in that: Including positive electrode sheet and electrolyte; The positive electrode sheet has a first surface and a second surface arranged opposite to each other in the thickness direction; the first surface has a plurality of concave portions, and the second surface has a plurality of convex portions; the positions of the concave portions on the first surface correspond to the positions of the convex portions on the second surface; the width of the concave portions is 0.2 mm-8 mm; The electrolyte includes a first carboxylate, and the first carboxylate includes propyl acetate; The depth h1 of the concave portion and the mass content c1 of the first carboxylic acid ester in the electrolyte satisfy: 5≤h1 / c1≤200, wherein the unit of h1 is μm.

2. The battery according to claim 1, wherein 10≤h1 / c1≤150; and / or, h1 is 3-40, and the unit of h1 is μm; and / or, c1 is 10%-80%; And / or, the spacing between the recesses is 0.5 mm to 8 mm; And / or, the width of the recess is 0.2 mm-4 mm; and / or, the height h2 of the convex portion is 2 μm-40 μm; And / or, the width of the convex portion is 0.2 mm-8 mm; And / or, the spacing between the protrusions is 0.5mm-8mm.

3. The battery according to claim 2, wherein 12.5≤h1 / c1≤75; and / or, h1 is 5-30, the unit of h1 is μm; and / or, c1 is 40%-60%; And / or, the spacing between the recesses is 1 mm-4 mm; and / or, h2 is 4 μm-30 μm; And / or, the width of the convex portion is 0.2 mm-4 mm; And / or, the spacing between the protrusions is 1mm-4mm.

4. The battery according to claim 1 or 2, wherein The electrolyte further includes a first lithium salt, wherein the first lithium salt includes at least one of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide.

5. The battery according to claim 4, wherein The first lithium salt includes lithium bis(fluorosulfonyl)imide; And / or, the mass contents c2 and c1 of the first lithium salt in the electrolyte satisfy: 2.5≤c1 / c2≤100; And / or, the mass content c2 of the first lithium salt in the electrolyte is 0.5%-10%.

6. The battery according to claim 5, wherein 5≤c1 / c2≤20; And / or, c2 is 2%-8%.

7. The battery according to claim 4, wherein The electrolyte further includes a first additive; The first additive includes at least one of 1,3-propane sultone, 1,3-propylene sultone, 2,4-butane sultone, 1,4-butane sultone, propylene sultone, butane sultone, methylene methanedisulfonate, dimethyl sulfate, vinyl sulfate, 4-methyl-vinyl sulfate, methyl vinyl sulfate, propylene sulfate and vinyl sulfite; and / or, the mass content c3 of the first additive in the electrolyte and the mass content c2 of the first lithium salt in the electrolyte satisfy: 0.07≤c2 / c3≤10; And / or, the mass content c3 of the first additive in the electrolyte is 0.1%-7%.

8. The battery according to claim 7, wherein 0.6≤c2 / c3≤2; And / or, c3 is 0.5%-5%.

9. The battery according to claim 1 or 2, wherein: The positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes first particles and / or second particles; The first particle includes a chemical formula of LiNi x1 Co y1 Mn z1 M 1 a1 O2 substances, 0.5≤x1≤0.95, 0.01≤y1≤0.2, 0.01≤z1≤0.4, 0≤a1≤0.1, M 1 including at least one of Al, Mg, Y, W, B, Zr, Ti, Sr, Si, La and Nb; The second particle includes a chemical formula of LiNi x2 Co y2 Mn z2 M 2 a2 O2 substances, 0.5≤x2≤0.95, 0.01≤y2≤0.2, 0.01≤z2≤0.4, 0≤a2≤0.1, M 2 Includes at least one of Al, Mg, Y, W, B, Zr, Ti, Sr, Si, La and Nb.

10. The battery according to claim 9, wherein The mass content of the first particles in the positive electrode active material is 50%-80%; and / or, the first particles include single crystal particles; and / or, the second particles include polycrystalline particles; and / or, the average particle size of the first particles is 1 μm-6 μm; and / or, the average particle size of the second particles is 6 μm-15 μm; And / or, the specific surface area of ​​the first particles is 0.5m 2 / g-1.4m 2 / g; And / or, the specific surface area of ​​the second particles is 0.3 m 2 / g-1m 2 / g.

11. The battery according to claim 1 or 2, wherein: The battery further comprises a separator, wherein the separator comprises a substrate layer and a glue layer; The glue layer is located on at least one outer surface of the separator, and the glue layer faces the positive electrode sheet; The thickness H1 of the adhesive layer and the depth h1 of the concave portion satisfy: 0.007≤H1 / h1≤0.6, wherein the unit of H1 is μm and the unit of h1 is μm.

12. The battery according to claim 11, wherein 0.02≤H1 / h1≤0.1, where the unit of H1 is μm and the unit of h1 is μm.

Citation Information

Patent Citations

  • Electrolyte and battery containing electrolyte

    CN110148788A

  • Positive electrode active material, preparation method thereof, lithium ion battery comprising positive electrode active material, battery module, battery pack and electric device

    CN116072829A

  • Secondary battery and electronic device

    CN116581284A

  • Electrochemical device and electronic device

    CN116802877A

  • Secondary battery and electronic device

    CN117134045A